Nature-Inspired Redox Shuttle with Regenerable Antioxidant for Efficient All-Perovskite Tandem Solar Cells - Meng, Rui; Du, Liming; Li, Can; Wan, Zhi; Shi, Jishan; Zhang, Yueying; Liu, Wenfeng; Zhi, Chongyang; Jia, Chunmei; Tan, Lili; Xiao, Chuanxiao; Wang, Xian‑Zong; et al. (Nano-Micro Letters, 2026)
Pb–Sn mixed perovskite solar cells (PSCs) are crucial components for realizing efficient all-perovskite tandem devices. However, their efficiency and stability are severely limited by oxidative degradation (Sn4+ formation) and metallic defects (Sn0/Pb0). In addition, the rapid and uncontrolled Sn2+ nucleation kinetics result in nonuniform crystallization. Herein, we introduce a natural redox shuttle glutathione (GSH) in Pb–Sn mixed PSCs, achieving regenerable antioxidation and crystallization regulation simultaneously. The reversible redox reactions between GSH and glutathione disulfide (GSSG) enable the self-healing of Sn4+ and Sn0/Pb0 impurities, creating a regenerable antioxidation protective shell at the perovskite interfaces. Meanwhile, the strong coordination between GSH and perovskite regulates the crystallization process, optimizing the nucleation and crystallization kinetics. Furthermore, the GSH incorporation creates a high-quality charge separation junction at the perovskite/hole transport layer, facilitating carrier separation and extraction. The optimized Pb–Sn PSCs exhibit impressive power conversion efficiencies (PCEs) of up to 23.71%. The champion all-perovskite tandem PSCs with GSH achieve a PCE of 28.49% and retain 90% of the initial PCE after 560 h of continuous illumination. This work establishes a new nature-inspired redox shuttling strategy and elucidates its working mechanism, advancing the development of efficient and stable all-perovskite tandem solar cells. Highlights: 1 A natural and regenerable redox shuttle is established using glutathione (GSH) to eliminate harmful Sn4+ and Sn0/Pb0 impurities. 2 The GSH incorporation regulates the perovskite crystallization process and leads to the formation of a high-quality charge separation junction. 3 The GSH-modified Pb-Sn perovskite solar cells achieve a champion power conversion efficiency (PCE) of 23.71%. Furthermore, the resulting all-perovskite tandem solar cells exhibit a PCE of 28.49% and retain 90% of the initial PCE after 560 h of continuous operation.